2018
DOI: 10.1128/aac.00547-18
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antibiofilm Efficacy of Graphene Oxide against Chronic Wound Microorganisms

Abstract: Chronic wounds represent an increasing problem worldwide. Graphene oxide (GO) has been reported to exhibit strong antibacterial activity toward both Gram-positive and Gram-negative bacteria. The aim of this work was to investigate the antimicrobial and antibiofilm efficacy of GO against wound pathogens. PECHA 10, PECHA 4, and X3 clinical isolates were incubated with 50 mg/liter of GO for 2 and 24 h to evaluate the antimicrobial effect. Optical and atomic force microscopy images were performed to visualize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 38 publications
8
56
0
1
Order By: Relevance
“…In a previous study, we demonstrated the antimicrobial and antibiofilm effect of GO against S. aureus PECHA 10, P. aeruginosa PECHA 4 and Candida albicans X3 single clinical isolates with a major effect against Staphylococci 12 . This major antimicrobial action against the Gram positive bacterium was demonstrated by AFM analysis that evidenced S. aureus cells wrapped by GO 12 , 23 . In addition, as reported by Song et al .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In a previous study, we demonstrated the antimicrobial and antibiofilm effect of GO against S. aureus PECHA 10, P. aeruginosa PECHA 4 and Candida albicans X3 single clinical isolates with a major effect against Staphylococci 12 . This major antimicrobial action against the Gram positive bacterium was demonstrated by AFM analysis that evidenced S. aureus cells wrapped by GO 12 , 23 . In addition, as reported by Song et al .…”
Section: Discussionmentioning
confidence: 87%
“…In LCWB model, GO is capable to interfere on the S. aureus and P. aeruginosa clustering in the dual species biofilm formation and it is also capable to disaggregate and disperse microbial sessile cells in the mature biofilm. Therefore, in the first phase of microbial colonization, GO can act delaying the infection process whereas, in the mature biofilm, GO can favour the disruption of the clustered bacteria embedded in the extracellular polymeric substances promoting the release of planktonic cells for which has been demonstrated the GO effect in terms of CFU reduction 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been attributed to different mechanisms, in which GO hinders the adhesion and penetration the biolm matrix, 65 and the Ag + ion is able to inhibit protein which then disrupts the synthesis of EPS that build up the biolm. In this study, the antimicrobial effect of chitosan could be overwhelmed by the AgGO, resulting in the greater anti-bacterial effect on Gram- negative bacteria.…”
Section: Anti-biolm Potentialmentioning
confidence: 99%